2003
DOI: 10.1002/app.11743
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic behavior of poly(vinyl alcohol) films with different molecular weights after UV irradiation, thermal annealing, and double treatment with UV irradiation and thermal annealing

Abstract: Pure poly(vinyl alcohol) (PVA) films with molecular weights 5,000, 72,000, and 125,000 g/mole were prepared by casting technique. The thickness of prepared samples was 0.21 mm. Xenon arc lamp was used to irradiate two samples from each molecular weight at 400 W for 5 min. One from each irradiated PVA samples was heated at 423 K for 2 h. An additional PVA sample unirradiated from each molecular weight was heated at 423 K for 2 h. Optical absorption measurements have been carried out in the wavelength range of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It was also observed that increasing PEG content into polymer blends increases the swelling ratios, and this is due to the increment in PVA hydrophilicity. In addition, it can be seen that the level of increase in swelling ratio (30,25,20, and 15 %) decreases with increasing PEG content (5, 10, 15, and 20 %). PEG is more hydrophilic than PVA so the swelling ratio increased with an increase in the molar ratio of hydrophilic groups of PEG component.…”
Section: Swelling Behavior and Gel Contentmentioning
confidence: 92%
See 1 more Smart Citation
“…It was also observed that increasing PEG content into polymer blends increases the swelling ratios, and this is due to the increment in PVA hydrophilicity. In addition, it can be seen that the level of increase in swelling ratio (30,25,20, and 15 %) decreases with increasing PEG content (5, 10, 15, and 20 %). PEG is more hydrophilic than PVA so the swelling ratio increased with an increase in the molar ratio of hydrophilic groups of PEG component.…”
Section: Swelling Behavior and Gel Contentmentioning
confidence: 92%
“…The C = O bands were attributed to the carbonyl functional groups due to the residual acetate groups remaining after the manufacture of PVA from hydrolysis of poly (vinyl acetate) or oxidation during manufacturing and processing [24]. The values of C = O and/or C = C peak intensities indicate that PVA have the same resonating structure from alkene↔alkane and C = O↔C-Oand/or presence of hydrogen bond with oxygen of C = O group [25]. The absorption band at 1436 cm -1 is assigned as CH 2 bending vibration while the deformation vibration of C-CH 3 is associated with the absorption band at 1348 cm -1 .…”
Section: Fourier Transform Infra Red (Ftir) Spectroscopic Investigationmentioning
confidence: 99%
“…PVA film practically does not absorb above 250 nm, which is obvious because of the very high hydrolysis degree of the rough polymer. Abd El Kader 44 reported that PVA samples in UV region, show two absorption bands at 284 and 327 nm, related to high energy absorption assigned as p-p* bonds (mainly C¼ ¼O and/or C¼ ¼C), which are present in the tail head of the polymer, and influenced by its molecular weight. The presence of cellulose in PVA matrix reduces the transmission capability of the polymer and this effect is influenced by the CNC content.…”
Section: Articlementioning
confidence: 99%
“…The UV peak is a signature of the van Hove singularity in the graphene density of states [32]. The PVA only shows significant absorption for shorter wavelengths [33]. Fig.2a plots a typical Raman spectrum of an exfoliated flake on Si/SiO 2 .…”
mentioning
confidence: 99%